Bilateral robots for upper-limb stroke rehabilitation: State of the art and future prospects. Issue 7 (July 2016) - Sheng, Bo; Zhang, Yanxin; Meng, Wei; Deng, Chao; Xie, Shengquan
Highlights: A comprehensive overview of robot mechanism for bilateral upper-limb rehabilitation robots since 1993. A systematic overview of clinical trials (total 34 randomized controlled trials and 877 participants) and effectiveness for robots described above. Several suggestions of robot mechanisms, clinical trials and directions for further researches. Abstract: Robot-assisted bilateral upper-limb training grows abundantly for stroke rehabilitation in recent years and an increasing number of devices and robots have been developed. This paper aims to provide a systematic overview and evaluation of existing bilateral upper-limb rehabilitation devices and robots based on their mechanisms and clinical-outcomes. Most of the articles studied here were searched from nine online databases and the China National Knowledge Infrastructure (CNKI) from year 1993 to 2015. Devices and robots were categorized as end-effectors, exoskeletons and industrial robots. Totally ten end-effectors, one exoskeleton and one industrial robot were evaluated in terms of their mechanical characteristics, degrees of freedom (DOF), supported control modes, clinical applicability and outcomes. Preliminary clinical results of these studies showed that all participants could gain certain improvements in terms of range of motion, strength or physical function after training. Only four studies supported that bilateral training was better than unilateral training. However, most of clinical results cannot definitely verify the effectiveness of mechanisms and clinical protocols used in robotic therapies. To explore the actual value of these robots and devices, further research on ingenious mechanisms, dose-matched clinical protocols and universal evaluation criteria should be conducted in the future.